2018
DOI: 10.1089/neu.2017.4988
|View full text |Cite
|
Sign up to set email alerts
|

Acute Clinical Predictors of Symptom Recovery in Emergency Department Patients with Uncomplicated Mild Traumatic Brain Injury or Non-Traumatic Brain Injuries

Abstract: There is a subset of patients with mild traumatic brain injury (mTBI) who report persistent symptoms that impair their functioning and quality of life. Being able to predict which patients will experience prolonged symptom recovery would help clinicians target resources for clinical follow-up to those most in need, and would facilitate research to develop precision medicine treatments for mTBI. The purpose of this study was to investigate the predictors of symptom recovery in a prospective sample of emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 87 publications
1
24
0
1
Order By: Relevance
“…Although it is well accepted that moderate to severe TBIs may cause permanent disability, [2][3][4] controversy exists surrounding the expected course of clinical recovery for patients with mTBI. In particular, although mTBI commonly causes acute symptoms, [5][6][7] cognitive dysfunction, 6,[8][9][10][11][12] and problems in day-to-day functioning, 13 findings vary as to whether patients continue to manifest sequelae of mTBI months to years postinjury. [14][15][16] Limitations in research methods have been proposed as a major factor explaining inconsistencies in the observed natural history of mTBI.…”
mentioning
confidence: 99%
“…Although it is well accepted that moderate to severe TBIs may cause permanent disability, [2][3][4] controversy exists surrounding the expected course of clinical recovery for patients with mTBI. In particular, although mTBI commonly causes acute symptoms, [5][6][7] cognitive dysfunction, 6,[8][9][10][11][12] and problems in day-to-day functioning, 13 findings vary as to whether patients continue to manifest sequelae of mTBI months to years postinjury. [14][15][16] Limitations in research methods have been proposed as a major factor explaining inconsistencies in the observed natural history of mTBI.…”
mentioning
confidence: 99%
“…Patients with persistent symptoms are treated at the MIBH for both TBI-related symptoms and changes in behavioral health, and the presence and expression of these symptoms can be understood through a neurobiopsychosocial model. 24 When considering persistent symptoms, there is a clear overlap of behaviors like impairment in sleep and memory in both concussion and psychological disorders. Sustaining an mTBI is tied to an increased risk of depression, sleep disorder, and memory dysfunction, just as depression, anxiety, and PTS are linked to changes in sleep and memory.…”
Section: Neurobiopsychosocial Modelingmentioning
confidence: 99%
“…For clinicians, prognostic models would assist in tailoring treatment plans to better suit the needs of the individual and, more importantly, facilitate the early provision of targeted treatment strategies to circumvent ongoing problems [20]. Moreover, researchers could use prediction models to help enrich clinical trials in order to accelerate the development of evidence-based therapies [21] that aim to prevent or ameliorate the effects of PPCS, as well as other neurodegenerative diseases that have been found to be associated with mTBI, such as Alzheimer's disease [22][23][24] and chronic traumatic encephalopathy [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of neuropsychological measures have also been examined as possible predictors of PPCS because cognitive deficits have been observed in both individuals who have sustained a mTBI [39,40] and those suffering from PPCS [41]. In particular, individuals who perform poorly on tasks of executive function [42], memory [33,[43][44][45], and psychomotor function [21] have been found to be at a heightened risk of developing PPCS. However, the fidelity with which neuropsychological measures can prognosticate PPCS has been questioned, as individual performance can be confounded by extraneous factors such as age, socio-economic status, and prior education [46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation